Isolasi, Karakterisasi, dan Uji Antioksidan Fungi Endofit dari Tanaman Batang Kunyit (Curcuma domestica Val.,) - Mahdalena Sy. Pakaya; Nur Ain Thomas; Hamsidar Hasan; Ariani H. Hutuba; Grasela Mbae (State University of Gorontalo, 2023)
Endophytic fungi live in mutualistic symbiosis and can produce secondary metabolites similar to their host. This research aims to isolate, characterize, and test the antioxidant activity of secondary metabolites from turmeric stems. This research is experimental research where the method used for endophytic fungi isolation is the direct planting method, and antioxidant activity is tested using qualitative and quantitative methods with DPPH (1.1-diphenyl-2-picylhydrazyl). One fungal isolate was obtained with the fungal isolate code (BK). Based on macroscopic and microscopic characterization, the BK fungal isolate indicates the Deuteromycota class's characteristics. The qualitative antioxidant test results indicate that the fraction of BK endophytic fungal isolate indicates antioxidant activity, indicated by the yellow color against a purple background on the TLC plate observed under visible light. The respective ICso values for the ethyl acetate and n-hexane fractions were 52.989 µg/ml and 89.725 µg/ml, categorized as strong antioxidants. The methanol fraction had an ICso value of 119.02 µg/ml, categorized as moderate, while the pure supernatant fraction had an ICso value of 156.86 µg/ml, categorized as weak antioxidant activity.